The Adult Student Population - Snyder, Fred A.; Blocker, Clyde E.; Harrisburg Area Community Coll., PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This study is concerned with the following topics on adult student attendance at Harrisburg Area Community College (HACC) during the 1969-70 academic year: student background, reason for attendance, enrollment in programs or courses, academic success, evidence of personal and occupational development. The report is based on the useable questionnaire responses from 998 credit and non-credit adult students, as well as their college records. The students' evaluation of HACC grew from their expectations, motivations, and experiences at the college. It was found that two premises for continuing education for adults are: (1) the need for renewing one's employment skills and abilities several times throughout life; and (2) the need to continually develop one's awareness of environment in terms of society, culture, and natural and technological phenomena. Recommendations reducing barriers for extending adult education are: off-campus centers, non-credit courses, financial aids, flexible admissions procedures, public information, and course scheduling. (CA)
Availability: Harrisburg Area Community College, 3300 Cameron Street Road, Harrisburg, Pennsylvania 17110 ($2.00).
Educational level discussed: Adult Basic Education.
Educational level discussed: Adult Education.
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Development; Adult Education; Adult Programs; Adult Students; Adult Vocational Education; Lifelong Learning; Two Year Colleges; Pennsylvania